Importance and attributions of nursing management in renal replacement therapy services: nurses' perception (Research, Society and Development, 2020)
Objective: To describe nurses' perception of the importance and attributions of nursing management in renal replacement therapy services. Method: Descriptive-exploratory research carried out in dialysis services in Belém and Ananindeua with nurse managers in this sector, through a semi-structured interview, with the interpretation of data based on Bardin's content analysis. Results: The research was carried out with 8 nurse managers of the dialysis service. Three categories emerged from the analysis: Category 1- Nurses' understanding of the management of nursing services in dialysis; Category 2- Category 2- The nurse's duties in the dialysis service; Category 3- The importance of nursing management in dialysis services. Conclusion: Nurses know their duties and the importance of their work, however, they cite adversities as obstacles in improving the quality of care.